PENGEMBANGAN VIDEO ANIMASI PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN ANIMAKER DI KELAS XI MAN 1 LANGSA - Robi N; Sofiyan; Rizki A (Universitas Samudra, 2023)
media, one of the learning media is audio-visual media or video animation. The study aims to develop animated videos for learning mathematics about sequences and series using Animaker and to determine the validity, practicality and effectiveness of the animation videos developed. This research method is Research and Development (R & D) with development models ADDIE that is Analysis, Design, Development, Implementation, Evaluation. The result of the study were in the the form of developing an animated video for learning mathematics using Animaker for student in class XI MAN 1 Langsa with an average validity test from media experts and material experts of 87.415% with very good criteria, practicality test results obtained an average of small-scale class trials and large-scale classes of 95.335% with very good criteria, the results of the effectiveness test in the form of pretest and posttest showed that the N-gain test results for the experimental class were 0.78 in the high category, while the N-gain test results for the control class were 0.33 n the medium category. This shows that video animation using Animaker is effective used in the learning process in class.